2018
DOI: 10.3390/sym10030061
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Anisotropy of the Media between Parallel Plates on the Casimir Force

Abstract: Quantum fluctuations of the electromagnetic field give rise to the force between parallel plates: the Casimir force. We theoretically calculate the Casimir force between two parallel isotropic plates when the space between the plates is filled with anisotropic material. Our result shows that the Casimir force, especially in the direction of the force, can be significantly affected by the anisotropy of the intervening material. We also discuss the combined influence of dispersion and anisotropy, and analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 24 publications
(86 reference statements)
2
15
0
Order By: Relevance
“…In one of our previous studies, the exact impact of the anisotropy of the intervening media on the Casimir force effect was calculated and the result showed that repulsive-attractive transition of the Casimir force could appear in this case and both the magnitude and the direction of the Casimir force were affected by the anisotropy of the intervening media [20]. In a subsequent work [21], we reinvestigated this problem when frequency-dependent permittivities were considered. We also discussed the influence of the external electric field on the Casimir force by affecting the anisotropy of the intervening media though the Kerr effect in that work [21].…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…In one of our previous studies, the exact impact of the anisotropy of the intervening media on the Casimir force effect was calculated and the result showed that repulsive-attractive transition of the Casimir force could appear in this case and both the magnitude and the direction of the Casimir force were affected by the anisotropy of the intervening media [20]. In a subsequent work [21], we reinvestigated this problem when frequency-dependent permittivities were considered. We also discussed the influence of the external electric field on the Casimir force by affecting the anisotropy of the intervening media though the Kerr effect in that work [21].…”
mentioning
confidence: 97%
“…In a subsequent work [21], we reinvestigated this problem when frequency-dependent permittivities were considered. We also discussed the influence of the external electric field on the Casimir force by affecting the anisotropy of the intervening media though the Kerr effect in that work [21]. The thermal Casimir force between two parallel isotropic plates separated by a uniaxial anisotropic film was investigated by Mostepanenko [22].…”
mentioning
confidence: 99%
See 3 more Smart Citations